Combination Treatment of Icariin and L-DOPA Against 6-OHDA-Lesioned Dopamine Neurotoxicity - Lu, Di-Sheng; Chen, Ce; Zheng, Ya-Xin; Li, Dai-Di; Wang, Guo-Qing; Liu, Jie; Shi, Jingshan; Zhang, Feng (Frontiers in Molecular Neuroscience, 2018)
Until now, the dopamine precursor, L-3, 4-dihydroxyphenylalanine (L-DOPA), remains the gold standard effective therapy for Parkinson’s disease (PD) patients. However, long-term chronic L-DOPA administration results in a loss of drug efficacy and severe adverse effects, including L-DOPA-induced dyskinesia (LID). Icariin (ICA) has been proved to evoke neuroprotection against dopamine (DA) neuronal loss in PD animal models. Here, the present study investigated the effects of ICA combined with L-DOPA on 6-hydroxydopamine (6-OHDA)-elicited DA neurotoxicity and L-DOPA-induced motor dysfunction as well. PC12 cells were applied to explore the combination treatment of ICA and L-DOPA against 6-OHDA-lesioned DA neurotoxicity. In addition, rat substantia nigral stereotaxic injection of 6-OHDA-induced DA neuronal damage was performed to investigate the neuroprotective effects of ICA combined with L-DOPA. The pathological movements triggered by L-DOPA were determined by the abnormal involuntary movements (AIM) scores analysis. In parkinsonian 6-OHDA lesioned rats, ICA conferred DA neuroprotection as monotherapy and an enhancement benefit of L-DOPA treatment after daily administration of L-DOPA and ICA for 21 days. Moreover, ICA ameliorated the development of LID as evidenced by the lowered AIM scores without affecting L-DOPA-mediated efficacy. Similar synergistical neuroprotection was shown in PC12 cells. Furtherly, ICA attenuated neuroinflammation in 6-OHDA-induced DA neuronal loss and the development of LID. In conclusion, these findings suggest ICA might be a potential promising adjuvant to enhance L-DOPA efficacy and attenuate L-DOPA-produced adverse effects in PD.